Perbandingan Pengelolaan Kinerja Keuangan Negara di Negara Berkembang dan Negara Maju (Studi Kasus Indonesia dan Singapura) - Hasibuan, Zalika Adinda; Dompak, Timbul; Salsabilla, Lubna (LPPM Universitas Putera Batam, 2024)
This research aims to compare the management of national financial performance in developing and developed countries through case studies of commercial banks in Indonesia and Singapore. This research uses a comparative descriptive approach by analyzing data from reliable sources. The results show that there are significant differences between developing and developed countries in terms of national financial performance management. It also shows that developed countries such as Singapore have a more stable and effective financial structure in managing financial performance, especially in terms of liquidity and financial risk monitoring. The national financial management system of developed countries is generally more transparent, accountable, and efficient than developing countries. On the other hand, developing countries such as Indonesia still face challenges such as limited resources and lack of effective supervision in managing financial performance. Singapore's financial policies are clearer and more consistent, and its financial structure is stronger and more stable. On the other hand, Indonesia still faces challenges in financial performance management such as limited resources and lack of effective supervision.